The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1186/s13071-017-2152-2
|View full text |Cite
|
Sign up to set email alerts
|

CD3+CD4negCD8neg (double negative) T lymphocytes and NKT cells as the main cytotoxic-related-CD107a+ cells in lesions of cutaneous leishmaniasis caused by Leishmania (Viannia) braziliensis

Abstract: BackgroundCutaneous leishmaniasis (CL) is caused by Leishmania (Viannia) braziliensis, which infects dermal macrophages and dendritic cells, causing an intense immune-mediated-tissue inflammation and a skin ulcer with elevated borders that can heal spontaneously or after antimonial therapy. The resolution of lesions depends on an adaptive immune response, and cytotoxic cells seem to have a fundamental role in this process. The aim of this study is to better understand the role of cytotoxicity mediated mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 52 publications
3
25
0
2
Order By: Relevance
“…In the current investigation we observed that LbAg induces CD3 + CD56 + NKT cell activation, leading to an expansion of cytotoxic-CD107a + CD3 + CD56 + NKT in all CL patient groups. Previous report of our group showed high percentages of total and cytotoxic-CD107a + NKT cells in the lesions of CL patients, reinforcing the involvement of NKT cells with cytotoxic activity in CL [20]. These findings together strengthen the important role CD3 + CD56 + NKT cells in the immune response established by the host during antimonial therapy, contributing to the resolution of disease [19,20].…”
Section: Plos Onesupporting
confidence: 83%
See 2 more Smart Citations
“…In the current investigation we observed that LbAg induces CD3 + CD56 + NKT cell activation, leading to an expansion of cytotoxic-CD107a + CD3 + CD56 + NKT in all CL patient groups. Previous report of our group showed high percentages of total and cytotoxic-CD107a + NKT cells in the lesions of CL patients, reinforcing the involvement of NKT cells with cytotoxic activity in CL [20]. These findings together strengthen the important role CD3 + CD56 + NKT cells in the immune response established by the host during antimonial therapy, contributing to the resolution of disease [19,20].…”
Section: Plos Onesupporting
confidence: 83%
“…Recently, our group investigated the contributions of cytotoxic CD4 + T, CD8 + T, NK and NKT cells in the immune response in blood from CL patients before, during and after antimonial treatment, highlighting an important cytotoxic activity by CD4 + T and NKT cells, differently from classical-cytotoxic cells, as CD8 + T and NK cells [19]. Corroborating this statement, we also reported the greatest contribution of CD4 neg CD8 neg T cells and NKT in the cytotoxic events in the CL lesion's milieu [20].…”
Section: Plos Onesupporting
confidence: 80%
See 1 more Smart Citation
“…Recent work has shown that cytotoxicity is one of the main mechanisms underlying disease induced by L. braziliensis infection ( Faria et al 2009 , Dantas et al 2013 , Novais et al 2013 , 2015 , Santos et al 2013 , 2015 , Cardoso et al 2015 , Ferraz et al 2015 , 2017 ) ( Table ). In a recent study performed by our group, we compared gene expression in lesions of patients with CL with that in normal skin from healthy individuals.…”
Section: Cytotoxic Activity and Pathogenesis Of CLmentioning
confidence: 99%
“…9 Furthermore, higher numbers of CD56 + cells are found in the peripheral blood of patients with CL before and after treatment, 10 as well as in lesions of patients with diffuse CL who have a positive response to immunotherapy. 11 Conversely, increased NK cell activity is linked to susceptibility and severity of human visceral leishmaniasis, 12 CL 13,14 and mucocutaneous leishmaniasis. 15 The pivotal balance that regulates either the functional activity of senescent CD8 + T cells or NK cytotoxic cells in blood and lesions of patients with CL is poorly understood.…”
Section: Introductionmentioning
confidence: 99%